1988
DOI: 10.1111/j.1365-2761.1988.tb00520.x
|View full text |Cite
|
Sign up to set email alerts
|

Histological effects of the inert suspended clay kaolin on the gills of juvenile rainbow trout, Salmo gairdneri Richardson

Abstract: Juvenile rainbow trout were exposed to 36, 171, 1017 and 4887 mg/1 of suspended kaolin clay for 64 days. Gills were analysed quahtatively and quantitatively using histology. Branchial pathology was absent at all sample times in fish exposed to 36,171 and 1017 mg/! kaolin, althoughintracellularkaotinwas visible within filament and lamellar epithelium in gills exposed to 171, 1017 and 4887 mg/1 kaolin at 4, 8, 16, 32 and 64 days. Lesions were found in gills exposed to 4887 mg/I kaolin at 16 and 32 days but the m… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

3
31
0
1

Year Published

1988
1988
2014
2014

Publication Types

Select...
9
1

Relationship

0
10

Authors

Journals

citations
Cited by 56 publications
(35 citation statements)
references
References 12 publications
3
31
0
1
Order By: Relevance
“…( X 500) irritants (Mallatt 1985). This is not surprising in light of the fact that gill lesions pathognomonic for particular agents or toxicants are rare (Goldes et al 1988).…”
Section: Discussionmentioning
confidence: 99%
“…( X 500) irritants (Mallatt 1985). This is not surprising in light of the fact that gill lesions pathognomonic for particular agents or toxicants are rare (Goldes et al 1988).…”
Section: Discussionmentioning
confidence: 99%
“…For species that remain in the disturbed area, elevated levels of sediment may have an adverse effect on fish health. Increased sedimentation and turbidity can reduce dissolved oxygen in the water column, and in extreme cases may cause a thickening of the gill epithelium and reduced respiratory function (Horkel and Pearson, 1976;Goldes et al, 1988;Waters, 1995). Increased mortality has been associated with increased suspended sediment for arctic grayling (T. arcticus), Atlantic silverside (Menidia menidia), rainbow trout (0. mykiss), fourspine stickleback (Apeltes quadracus), white perch (Morone americana), yellow perch (Perca flavescens), American shad (Alosa sapidissima), striped bass (M. saxatilis), coho salmon (0. kisutch), chinook salmon (0. tshazuytscha), chum salmon (0. keta), striped killifish (Fund&s majalis), sheepshead minnow (Cyprinodon variegatus), and even carp (Cyprinus caqio) (Newcombe, 1994;Newcombe and Jensen, 1996).…”
Section: Ill Effectsmentioning
confidence: 99%
“…Goldes et al (1988) reported moderate to severe gill infestations by the ectoparasitic flagellate Ichtyobodo necator in rainbow trout exposed to high levels of inert suspended solids in the form of clay kaolin, whereas fish kept in otherwise identical conditions were not infested. Many coho salmon with prominent Paramoeba infestations in our study were also infected with a microsporidium (Loma salmonae) or a monogenean (Laminiscus strelkow~].…”
Section: Transmissionmentioning
confidence: 99%